Dumb Blonde Effect : How Stereotypes and Needlessly Complex Words are Associated - Toddes, Carlee; Custer, Taylor (My University, 2013)
The purpose of this study was to examine whether exposing participants to images of blonde-haired women caused them to perform poorly on a cognitive task, and whether increasing the difficulty level of the vocabulary in an essay causes an author to be perceived as less intelligent.
Color poster with text, charts, and graphs.
Keywords: Dumb blonde stereotype; Perception; Posters